Distribution and concentrations of Ni in tissues of the gastropod Nerita lineata collected from intertidal areas of Peninsular Malaysia - Cheng, Wan Hee; Yap, Chee Kong; Ahmad, Ismail; Ismail, Abdul Rahim (Universiti Putra Malaysia Press, 2012)
Nickel (Ni) is an essential metal but not a well-studied metal in gastropods. In this study, Nerita lineata snails were collected from 20 sites along the western coast of Peninsular Malaysia from December 2005 to December 2010. The concentrations of Ni were determined in the total soft tissues, opercula and shells of the snails. Different patterns of Ni distribution were found in different tissues (shells, opercula and soft tissues) as well as spatial differences and distributions. This finding showed that the distributions of Ni in the shells and total soft tissues of N. lineata were significantly different, and this could be due to the different rates of Ni accumulation, excretion and sequestration. Since N. lineata can be abundantly found in rocky shores, below jetties and mangrove trees along the intertidal areas of the west coast of Peninsular Malaysia and it can show the ability to accumulate Ni, the snails can therefore act as potential biomonitors of Ni pollution in the western coast of Peninsular Malaysia.